Isolation of cyanide‐degrading bacteria and molecular characterization of its cyanide‐degrading nitrilase. (21st January 2021) - Terada, Ayane; Komatsu, Daisuke; Ogawa, Takahiro; Flamandita, Darin; Sahlan, Muhamad; Nishimura, Minoru; Yohda, Masafumi
Abstract: Hydrogen cyanide is an industrially important chemical, and its annual production is more than 1.5 million tons. Because of its toxicity, the cyanide‐containing effluents from industries have caused many environmental problems. Among various methods to treat the contaminated soils or water, the biological degradation is regarded to be promising. We isolated two cyanide‐degrading microorganisms, Pedobacter sp. EBE‐1 and Bacillus sp. EBE‐2, from soil contaminated with cyanide. Among these bacteria, Bacillus sp. EBE‐2 exhibited significantly a high cyanide‐degrading ability. Bacillus sp. EBE‐2 might be used for the remediation of cyanide contaminated water or soil. A nitrilase gene was cloned from Bacillus sp. EBE‐2. Bacillus nitrilase was expressed in Escherichia coli and purified. Bacillus nitrilase exhibited cyanide‐degrading activity as a large oligomer. Since formic acid formation from cyanide was observed, Bacillus nitrilase is likely to be a cyanide hydrolase. Although there exist various homologous enzymes annotated as carbon–nitrogen family hydrolases, this is the first report on the cyanide degrading activity. The structure and catalytic site of Bacillus nitrilase were studied by homology modeling and molecular docking simulation. Abstract : Two cyanide‐degrading microorganisms, Pedobacter sp. EBE‐1 and Bacillus sp. EBE‐2, were isolated from soil contaminated with cyanide. Among these bacteria, Bacillus sp. EBE‐2 exhibited significantly a high cyanide‐degrading ability with cyanide hydrolase.